Translating Growth Into Poverty Reduction beyond numbers - Kessy, Flora (Dar es Salaam Mkuki na Nyota Publishers, 2013)
Tanzania is a politically stable, much aided country that has consistently grown economically during the first decade of the millennium, while also improving its human development indicators. However, poverty has remained persistent, particularly within rural areas. This collaborative work delves into the reasons why this is so and what can be done to improve the record. The book is the product of both Tanzanian and international poverty experts, based on largely qualitative research undertaken within Tanzania by the Chronic Poverty Research Centre (CPRC). The authors highlight and discuss the importance of macro- and micro-level causes of the persistence of poverty. The latter, on which the book is focused, centre around a negative dynamic affecting a large number of poor households in which widespread failure to provide household food security undermines gender relationships and reduces the possibility of saving and asset accumulation which is necessary for escaping poverty. This results in very low upward mobility. Vulnerability is widespread and resilience against shocks minimal, even for those who are not absolutely poor. Through an in-depth and broad analysis of poverty in Tanzania, the book provides alternative conclusions to those often repeated in the poverty discourse in international and local arenas. The conclusions were reached with the specific aim of informing political and policy debates within Tanzania.
Keywords: Poverty